Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Keputusan Pembelian Pada Toko Buah King Fresh (Studi Kasus Konsumen Toko Buah King Fresh, Samarinda, Kalimantan Timur) - Salma Khaulan Fadillah; M. Zaini (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the influence of service quality, price, and location on consumer purchasing decisions at King Fresh Fruit Store Samarinda. This research employed a quantitative approach using a survey method. The sample consisted of 100 respondents selected through a simple random sampling technique. Data were analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS). The results indicate that service quality, price, and location have a positive and significant effect on consumer purchasing decisions. Simultaneously, the three independent variables significantly influence purchasing decisions. Price is identified as the most dominant variable affecting consumer purchasing decisions. The coefficient of determination test shows that service quality, price, and location explain 63.7% of purchasing decisions, while the remaining 36.3% is influenced by other factors outside the research model.